Septic pulmonary embolism secondary to klebsiella pneumoniae epididymitis: Case report and literature review. (2019)
Background. Septic pulmonary embolism (SPE) is defined as the occurrence of septic thrombi in the pulmonary circulation. We report a case of SPE secondary to K. pneumoniae epididymitis. Case Presentation. A 74-year-old male with a history of diabetes mellitus experienced SPE secondary to epididymitis, with isolation of K. pneumoniae in blood and presence of lung nodules, with a chest computed tomography showing the halo and reversed halo signs. Discussion. SPE is characterized by the presence of septic thrombi in the pulmonary circulation coming from an extrapulmonary infective focus. SPE secondary to K. pneumoniae epididymitis is an uncommon condition that is characterized by the presence of multiple bilateral nodules of peripheral distribution. Conclusion. SPE is an unusual complication of acute epididymitis. Suspicion of SPE should be considered in patients with a diagnosis of epididymitis, respiratory symptoms, and multiple nodules in chest imaging assessments.